Analysis of the Influence of Cash Management on Liquidity in the F&B Sector of MSMEs in Bandung City - Dodi Tisna Amijaya; Rudi Suprianto Ahmadi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to examine the impact of Cash Management on Liquidity in Micro, Small, and Medium Enterprises (MSMEs) operating in the Food and Beverage (F&B) sector in Bandung City, while investigating the moderating effect of Product Type. The investigation employed a quantitative methodology, using simple linear regression analysis techniques for Model 1, and multiple linear regression for Model 2, which incorporates interaction variables. The findings show that Cash Management exerts a positive and statistically significant influence on Liquidity, as evidenced by the R Square value of 0.363. In addition, the inclusion of the interaction variable of Cash Management and Product Type in Model 2 resulted in an increased R-Square value of 0.420, thus reflecting the increased capacity of the model to explain variations in Liquidity. The interaction variable of Cash Management with Product Type was also shown to have a significant effect, thus strengthening the relationship between Cash Management and Liquidity. Based on these findings, it can be concluded that proficient cash management is critical to improving the liquidity of F&B MSMEs. Moreover, the nature of the products sold serves to moderate this relationship; consequently, it is important for cash management strategies to be tailored to the specific attributes of the products. This research provides practical contributions to MSMEs by facilitating the optimization of their financial management practices.